THE FORMULA FOR THE COMPLETE STRESS-STRAIN DIAGRAM FOR COMPRESSIVE CONCRETE UNDER FIRE AND HIGH TEMPERATURE CONDITIONS (MODERN CONSTRUCTION AND ARCHITECTURE, 2022)
The theory of calculating reinforced concrete structures for fire resistance in general is not fully developed. Among the calculation methods outlined in the design standards and divided into tabular data, simple and advanced methods are relatively developed in the first and second groups. But the advanced methods are not described at all, but have only basic requirements. The problems of developing advanced methods for calculating the fire resistance of reinforced concrete structures is due to: firstly, nonlinear strength, deformation, thermophysical and thermomechanical properties of concrete and reinforcing steel and their change with temperature; secondly, by non-linear temperature effects caused by a fire and, accordingly, by non-linear non-stationary processes of heat exchange, which as a result gives a non-linear distribution of heat fields in the volume or cross-section of the element.One of the reasons that inhibits the development of refined methods for calculating the fire resistance of reinforced concrete structures, according to the authors of the current article, is the lack of a clear analytical description (formula) of the complete (including ascending and descending branches) stress-strain diagram for concrete, in fire conditions and at high temperatures. Such a formula must meet the requirements formulated and substantiated in previous theoretical studies.The article is devoted to obtaining the formula for the complete stress-strain diagram for concrete compression, under fire conditions and at high temperatures. Obtaining the formula is based on the knowledge set forth in the design standards at normal temperatures and the authors' previous research, which becomes their logical continuation. The received formula was verified against the requirements formulated in previous studies and compared with experimental data. Analytical dependences for temperature coefficients were also obtained, and their comparison with the data contained in the design standards was performed.The obtained results can be used both in the development of new fire resistance calculation methods, related to the refined ones, and in the existing ones, as an alternative to the generally known data. It is also possible to use it in calculation computer programs to describe the deformation of uniaxial compression of concrete at different temperatures and with a temperature gradient.
Keywords: stress-strain diagram; concrete; high temperatures; fire.